Landscapes of Freedom : Building a Postemancipation Society in the Rainforests of Western Colombia - Leal, Claudia, 1970- (Latin American landscapes., 2018)
After emancipation in 1851, the African descendants living in the extra-humid rainforests of the Pacific coast of Colombia attained levels of autonomy hardly equaled anywhere else in the Americas. This autonomy rested on their access to a diverse environment--including small strips of fertile soils, mines, forests, rivers, and wetlands--that contributed to their subsistence and allowed them to procure gold, platinum, rubber, and vegetable ivory for export. Afro-Colombian slave labor had produced the largest share of gold in the colony of New Granada. After the abolishment of slavery, some free people left the mining areas and settled elsewhere along the coast, making this the largest area of Latin America in which black people predominate into the present day. However, this economy and society, which lived off the extraction of natural resources, was presided over by a very small white commercial elite living in the region's ports, where they sought to create an urban environment that would shelter them from the jungle. Landscapes of Freedom reconstructs a nonplantation postemancipation trajectory that sheds light on how environmental conditions and management influenced the experience of freedom. It also points at the problematic associations between autonomy and marginality that have shaped the history of Afro-America. By focusing on racialized landscapes, Leal offers a nuanced and important approach to understanding the history of Latin America.